Factores que intervienen en el procesamiento del semen bovino durante su congelación - Aguirre M, Martha; Anderson, Steven William; Huertas V., Ernesto (Instituto Colombiano Agropecuario - ICA, 2019)
In this work we tried to find the better moment for the freezing and so we did-1440 analisis from 3 1-lolstein bulls, I Normandy and I San Martinero. All the steps in the freezing process were studied, since the adition of part of the extender to the raw semen and at one hour intervals before the freezing and post-thawing after de adition of the glicerolated extender. Tile final exam was made at 22 hours of the equilibration time. The parameters studied were motility, percentaje of live-dead sperms. acrosome morphology and the release of the intracelular glutamie oxaloacetic Iransaminase (G.O.T.) enzyme. The higest sperm mortality in the prefreezing stage was at 22 hours, but the survival after thawing gave the best results at 4 and 22 hours and the minimun values at the first hour of the equilibration period. The G.O.T. analisis showed the higest release of the enzyme when semen was frozen at 2 hours and the minor value at 4 hours, but it was not statistically significant with the other hours of freezing. The minimum acrosomic damage was obtained during the freezing at 2 hours and at 4 hours and it was observed the higest percentaje of motility.